POTENTIAL PRODUCTION OF OIL FROM WASTE PLASTIC PYROLIYSIS IN GEOSTECH BUILDING - Kristyawan, I Putu Angga (BPPT, 2016)
Office waste is produced from activity that carried in the office area. In Geostech office area, 18.05 % composition of the waste is plastic waste. Plastic waste total in Geostech is 17.1 kg/week. The highest of plastic waste type is PP (Polypropylene). plastic waste. From the waste total is known that that the potential of oil produced through pyrolysis is 11.6 kg/week or 13.7 L/week. Pirolysis oil can be used as substitute for diesel fuel because of the calorific value equal with the calorific value of diesel fuel. Besides oil, pirolysis of Geostech office plastic waste is also potential to give 5.45 kg/week gas product.Key words : waste, office, pirolysis, oil